PESAN DAKWAH PADA FILM MERINDU CAHAYA DE AMSTEL - Haq, Maulaya Arinil; Syaripah, Imroatus (Universitas Muhammadiyah Kotabumi, 2023)
In the last few decades, the film industry has experienced rapid progress and has played an important role in the field of communication or conveying messages. Where initially it was just a black and white image, it then developed with all kinds of effects that made the film look more real, making it more interesting for the audience to enjoy. In more detail, film is a communication medium in the form of moving images. One film that conveys the message of preaching is the film Merindu Cahaya De Amstel, directed by Hadrah Daeng Ratu, which is an adaptation of a novel by Arumi Ekowati which is based on a true story. This film takes the background of a non-Muslim woman who changed her name to Siti Khadijah after embracing Islam. In this study we used qualitative research. This approach aims to find and describe religious elements. The data source for this research is films and the data for this research are words, phrases, clauses, sentences, paragraphs and dialogues that describe religious elements contained in the film Merindu Cahaya De Amstel. This research data collection technique uses library research. After data collection, data analysis is carried out by following the data analysis steps, namely classifying, describing and concluding. In this film there are several preaching messages, namely that a woman must cover her private parts and be friends with others who help each other in goodness, and remember that the commands from Allah SWT are the most important, especially when receiving messages of goodness that must be spread widely and become useful human beings.